Bioavailability of a Capsaicin Lipid Multi-particulate Formulation in Rats - Şahin, Kazım; Küçük, Ömersman; Orhan, Cemal; Sahin, Emre; Fowler, Kelli; White, Tyler; Bellamine, Aouatef (Springer France, 2021)
Background and Objective Because of the stomach-burning sensation it induces, capsaicin has been used at relatively low doses as a nutritional supplement, which has limited its bioavailability. The objective of this study was to investigate the serum bioavailability of capsaicin supplementation with or without a lipid multi-particulate (LMP) formulation. Methods Thirty-five rats were divided into five groups and administered capsaicin at either 0.2 or 1 mg/kg with or without the LMP formulation. Capsaicin bioavailability was assessed based on the area under the concentation-time curve (AUC), the time to peak concentration (T-max), and the peak serum concentration (C-max). Results For each formulation, the capsaicin C-max was reached at 90 min and decreased thereafter. Serum capsaicin concentrations were greater in rats administered the higher dose of capsaicin (1 mg/kg) in the LMP formulation at all measurement times (P <= 0.05). The AUC showed a significant increase, about 20%, when capsaicin was administered in the LMP formulation at the high dose (P = 0.002). The T-max for oral capsaicin was similar whether or not administration was via the LMP formulation (P = 0.163). However, the C-max of capsaicin increased in a dose-dependent manner (P < 0.05). Although the LMP formulation of the high dose of capsaicin resulted in a numerically higher C-max, it was not statistically significantly higher (P = 0.068). Conclusions The present work demonstrated that administration of capsaicin via the LMP formulation significantly impacted the pharmacokinetic parameters and the serum bioavailability of orally administered 1 mg/kg capsaicin in rats. The bioavailability of capsaicin in humans may also be increased by using the LMP formulation.
Keywords: Oral Bioavailability; Topical Delivery; in-Vitro; Release; Carriers; Tissue